Kekerasan Seksual di Lingkungan Pendidikan: Dampak dan Strateginya di Indonesia (Lembaga Pengembangan Kinerja Dosen, 2026)
Cases of sexual violence are rife in educational environments and generally happen to women. Ironically, 55% of sexual violence perpetrators are committed by teachers, in fact many cases are still unreported. Preventing sexual violence is a shared responsibility. This study aims to determine the conditions, impacts and strategies that can be used to prevent sexual violence. A qualitative analytical approach with secondary data in the form of interviews broadcast via the Narasi TV and YouTube websites (Crime Lab, COKRO TV, KAWANUATV MANADO, Tribun Health, UNPAR OFFICIAL) was used in this research. The impacts felt by victims of sexual violence include feeling afraid, embarrassed, depressed, traumatized and low self-esteem. Strategies that can be implemented include promoting social norms, implementing social emotional learning related to sexual violence, forming a task force, mentoring support in the form of counseling and medical services as well as parental supervision and assistance. Mutual cooperation and synergy need to be carried out together to create a school environment that is safe and comfortable for students and free from sexual violence.